2019
DOI: 10.5539/jas.v11n17p251
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality of Underground Wells in Limoeiro do Norte, Brazilian Northeast

Abstract: The objective of this work was to assess the physicochemical and microbiological characteristics, as well as the potential of salinization and sodification of groundwater wells in Limoeiro do Norte, Ceará states, Brazil. Six water wells were selected for the study, all of them used for irrigation and human consumption. The ionic classification was performed by Piper Diagram and the salinity risk using the U.S.S.L. (United States Salinity Laboratory) Diagram using Qualigraf software. Based on the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…and SO 4 2-) are prevalent in waters of the Brazilian Semiarid region (Rodrigues et al, 2019). Studies have reported successful use of preparation of nutrient solutions for the growth of several leafy vegetables, such as coriander and rocket (Campos Júnior et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…and SO 4 2-) are prevalent in waters of the Brazilian Semiarid region (Rodrigues et al, 2019). Studies have reported successful use of preparation of nutrient solutions for the growth of several leafy vegetables, such as coriander and rocket (Campos Júnior et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%